Asset price bubbles in the perspective of New Keynesian theory. Summary: Varade hinnamullid ja reaalkurss majanduskoolkondade lähenemiste valguses - Angerma, Meelis (Estonian Discussions on Economic Policy, 2013)
Developments in the real world depends on human reaction to economic events which is also determined by dominating economic thought. Dominance of neoliberal and monetarist thinking was the main cause of ignoring asset price bubbles and their effects on real economy. New keynesian economic thinking provides an alternative. Hyman Minsky’s model of financial instability was more effectively able to explain super-bubbles in US economy and subsequent ‚Great Recession’. Ignorance of momentum-bias of traders and banks contributed to this crises. Emerging markets and Baltic countries were strongly influenced by credit oversupply in US. Instabilities were so sizeable that IMF approved using capital control and proposal for tax on financial transactions was made. Policymakers and individuals should abandon ignorance of speculative asset price bubbles and improve their analytical skills to recognize bubbles and change their behaviour